The Role of Gene Therapy in the Treatments of Type 1 Diabetes Mellitus: a review - Harem Othman Smail (Biology, Medicine, & Natural Product Chemistry, 2020)
The main aims of this review were to understand the roles of gene therapy in the treatment and prevention of type 1 diabetes mellitus and I will discuss a brief history, approaches, vector types with the future of diabetes following clinical use. Type 1 diabetes mellitus is a metabolic condition that is identified by insufficient insulin development due to pancreatic damage to beta cells. Control, long life, and diagnosis of these metabolic disorders have become vital sources for many scientists and researchers. After 2000, the latest approaches to molecular medicine were introduced as one of the possible therapeutic options for diabetes type 1 diagnosis. Many genes have been reported as a clinical trial so that damaged genes can be treated and three main approaches shown about 50 years ago are islet transplantation, β cell regeneration, and insulin gene therapy to cure and prevent diabetes type. Treating diabetes through gene therapy can promise children and adolescents, but more clinical applications are needed to recognize it as a permanent route.